PENGARUH KUALITAS LABA, INCOME SMOOTHING, DAN FINANCIAL DISTRESS TERHADAP NILAI PERUSAHAAN - Saputra, Indra; Andani, Mega (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This purpose of this study was to found whether effect Profit Quality, Income Smoothing, and Financial Distress on Company Value (Empirical Study of Mining Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period). The sample drawn by purposive sampling and fulfill sample selection criteria. Methods of data analysis using multiple linear regression method. The results of the study show that the variable Earning Quality has an effect on Firm Value, while the Income Smoothing and Financial Distress variable has no effect on Firm Value. The results of simultaneous research on Profit Quality, Income Smoothing, and Financial Distress has an effect on Firm Value.